Worldwide Hot Mix Asphalt Layer Application and Scrap Rubber and Bitumen Emulsion Studies on Railway Track-Bed - Dian M Setiawan (Semesta Teknika, 2018)
Researchers around the world have performed various studies on reinforcement of track-bed and mitigation of ballast deterioration. This paper objective is to conduct a literature review comprehensively to analyse and discuss the development of rubber, bitumen emulsion, and asphaltic layer usage on railway track-bed to study the proposed alternative of Indonesian unconventional rail track design concept. Various asphalt track-bed concept around the world have been reviewed (Germany, USA, Italia, Japanese, France, Spain, and Austria). Research on scrap rubber and bitumen emulsion in railway track-bed also examined in this paper. There are no researchers’ uses these three methods together in their study. In fact, each design has its benefits and limitations, so if these three methods are combined, then they will complete each other and will produce better output. The author suggests developing a new track structural components design that combined asphalt layer, scrap rubber, and bitumen emulsion. This new design expected to have capabilities to serve high-speed railway and existing railway track corridors more cost-effectively compare to the conventional tracks in consequence of their potential to have greater structural stability, considerably lower maintenance works, and more service-life. It can serve the train journey with higher speed and higher axle load.